Early diagnosis of grade-3 oligodendroglioma and its management: an uncommon tumor in an unlikely age: a case report - Karna, Anish; Yadav, Rajesh; Kshetri, Samir (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Glioma, a type of primary brain tumor, often presents subtly but can progress silently if not caught early. This case highlights a young female who initially experience dull right-sided headache for over a week, later followed by sudden episodes of projectile vomiting and dizziness. CT scan revealed a suspicious frontotemporal mass, which was later diagnosed as Grade-3 oligodendroglioma through diagnostic and therapeutic right pterional craniotomy and immunohistochemistry. She underwent timely surgical intervention and is now receiving radiation therapy with government support. This case underscores the value of early diagnosis and coordinated care, especially in people with low socioeconomic status.